Peran Laporan Keuangan Dalam Perencanaan dan Pengendalian Manajemen - Ferdy Nanda Syahputra; Lucy Asriani; Ersi Indriani; Roy Ridoy Ramadhan Marpaung; Muhammad Rivaldi (MUARA EKONOMI : Jurnal Ilmiah Ilmu Ekonomi, Manajemen & Bisnis, 2025)
Financial statements play an important role in supporting management planning and control functions. This article aims to examine the role of financial statements in management planning and control based on a literature review of national journals published between 2020 and 2025. The research method used is a literature study by reviewing articles discussing the utilization of financial statements, accounting information systems, internal control, and human resource competence. The results indicate that financial statements are used as a basis for budgeting, performance target setting, and monitoring and controlling organizational activities. The effectiveness of financial statement utilization is strongly influenced by report quality, human resource competence, and internal control systems. Therefore, financial statements should be optimally utilized as managerial tools in planning and control processes